2013
DOI: 10.1111/jcmm.12027
|View full text |Cite
|
Sign up to set email alerts
|

Mechanobiology in cardiac physiology and diseases

Abstract: Mechanosensitivity is essential for heart function just as for all other cells and organs in the body, and it is involved in both normal physiology and diseases processes of the cardiovascular system. In this review, we have outlined the relationship between mechanosensitivity and heart physiology, including the Frank–Starling law of the heart and mechanoelectric feedback. We then focused on molecules involved in mechanotransduction, particularly mechanosensitive ion channels. We have also discussed the involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 93 publications
0
60
0
1
Order By: Relevance
“…The application of specific physical stimuli in a tailored bioreactor emerged as an appropriate strategy to obtain a bioengineered cardiac tissue, where mechanotransduction is known to play a significant role [37]. The initial evidence of effectiveness of mechanostimulation protocols in cardiac tissue engineering dates back to the second half of the nineties, when Vandenburgh et al [38] showed that unidirectional mechanical stretch initiated in vitro a number of morphological alterations in a confluent cardiomyocyte population which were similar to those occurring during in vivo heart growth.…”
Section: Bioreactors For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…The application of specific physical stimuli in a tailored bioreactor emerged as an appropriate strategy to obtain a bioengineered cardiac tissue, where mechanotransduction is known to play a significant role [37]. The initial evidence of effectiveness of mechanostimulation protocols in cardiac tissue engineering dates back to the second half of the nineties, when Vandenburgh et al [38] showed that unidirectional mechanical stretch initiated in vitro a number of morphological alterations in a confluent cardiomyocyte population which were similar to those occurring during in vivo heart growth.…”
Section: Bioreactors For Cardiac Tissue Engineeringmentioning
confidence: 99%
“…Beyond this, the importance of mechanoelectric feedback adds another layer of complexity to cardiac mechanotransduction. For instance, ion channels such as Cav1.2 and the TRP family of ion channels have specific locations in the heart and enable organ level responses to pressure and volume fluctuations by helping regulate action potentials (Takahashi et al, 2013). Connexins, transmembrane proteins important for gap junction formation, may act as effectors to coordinate excitation-contraction coupling (Meens et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…165 It has been implicated in stretch-activated responses of vascular smooth muscle. 179 Overexpression of TRPM4 may be involved in an inheritable form of progressive familial heart block type I, 67 though perhaps via mechanisms not directly related to TRPM4 mechano-sensitivity. Its physiological role in the heart is currently unknown.…”
Section: Cardiac Sac: Molecular Candidatesmentioning
confidence: 99%
“…66 Interestingly, stretch-preconditioning, known to reduce ischaemia-reperfusion injury, is abolished by blocking K ATP channels. 67 Of note, cardiac K ATP channels are also present and active in fibroblasts, suggesting that one must consider cardiac pre-/post-conditioning effects on cells other than just cardiomyocytes. 6870 As with other K + channels, K ATP opening favours re-/hyperpolarization.…”
Section: Introduction To Cardiac Mechano-sensitivitymentioning
confidence: 99%